2013
DOI: 10.1038/gt.2013.52
|View full text |Cite
|
Sign up to set email alerts
|

Minimal piggyBac vectors for chromatin integration

Abstract: We describe novel transposon piggyBac vectors engineered to deliver transgenes as efficiently as currently available piggyBac systems, but with significantly less helper DNA co-delivered into the host genome. To generate these plasmids, we identified a previously unreported aspect of transposon biology, that the full-length terminal domains required for successful plasmid-to-chromatin transgene delivery can be removed from the transgene delivery cassette to other parts of the plasmid without significantly impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 21 publications
1
32
2
Order By: Relevance
“…Nonetheless, our findings of a high rate of transposase integration when using a ‘cis’ configuration are important as the use of PB for genome modification increases and ‘cis’ plasmid vectors are available. A recent investigation reported integration of ‘minimal’ PB components when full-length TRs are provided elsewhere in the plasmid; however, these results can be explained via our observation of transposon plasmid backbone DNA integration ( 33 ).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Nonetheless, our findings of a high rate of transposase integration when using a ‘cis’ configuration are important as the use of PB for genome modification increases and ‘cis’ plasmid vectors are available. A recent investigation reported integration of ‘minimal’ PB components when full-length TRs are provided elsewhere in the plasmid; however, these results can be explained via our observation of transposon plasmid backbone DNA integration ( 33 ).…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, we observed no mobilization of endogenous human genomic DNA by the PB transposase using colony count assays, excision assays and double-stranded DNA break assays. Further refinement of PB vectors has demonstrated that shortening the 5′TR to 35 bp and the 3′TR to 63 bp may still mediate gene transfer ( 33 ). It is likely that a high degree of sequence specificity is required to mediate transposition from both TRs.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we detailed its construction and demonstrated its ability to transpose cells as efficiently as full-length piggyBac transposons 11 ; we also demonstrated that this vector can be used for the rapid generation and purification of packaging cells capable of stably producing self-inactivated gamma-retroviruses. 26 Here, we show that this vector can be used to successfully integrate a 15 kb transgenic sequence into target cells, twice the capacity of retroviral vectors which are currently the most popular method for stable gene delivery.…”
Section: Discussionmentioning
confidence: 99%
“…10 Recently, we developed a modified piggyBac delivery system in which most of both terminal domains were relocated from the delivery cassette into the helper (nonintegrating) part of the same plasmid to minimize the size of the delivered transposon; this was accomplished without a significant loss of transposition efficiency. 11 Despite the reduction in the size of the delivered fragment, these minimal piggyBac plasmids include all the required elements for transposon integration. Like classical piggyBac plasmids, these minimal piggyBac vectors have two segments—one segment that is integrated and one that facilitates this integration.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we developed a modified piggyBac transposon delivery system in which the transposase gene and most of both terminal domains were relocated from the delivery cassette into the helper (non-integrating) part of the same plasmid without a significant loss of transposition efficiency [ 17 ]. Similar to classical piggyBac vectors, these truncated (minimal) transposon vectors can deliver a large amount of transgenic DNA, yet incorporate significantly less helper DNA (fewer than 100 base pairs) than classical piggyBac vectors or retroviruses.…”
Section: Introductionmentioning
confidence: 99%